2023
DOI: 10.1021/acs.biomac.2c01381
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Microglial Attenuation through Dendrimer–Drug Conjugates Improves Glaucoma Neuroprotection

Abstract: Retinal microglial/macrophage activation and optic nerve (ON) microglial/macrophage activation are glaucoma biomarkers and potential therapeutic targets for this blinding disease. We report targeting of activated microglia by PAMAM dendrimers in a rat glaucoma model and neuroprotection by N-acetylcysteine-conjugated dendrimer (D-NAC) conjugates in a post-injury rescue experiment. Intravitreally delivered fluorescently labeled dendrimer (D-Cy5) conjugates targeted and were retained in Iba-1-positive cells (90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…Studies have found that slow release of GDNF and CNTF with nanotechnology can extend the duration of efficacy and significantly improve RGC survival in animal glaucoma models [109][110][111][112]. Nanomedicine has also improved delivery of antioxidant compounds used to treat glaucoma [113][114][115][116]117…”
Section: Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that slow release of GDNF and CNTF with nanotechnology can extend the duration of efficacy and significantly improve RGC survival in animal glaucoma models [109][110][111][112]. Nanomedicine has also improved delivery of antioxidant compounds used to treat glaucoma [113][114][115][116]117…”
Section: Nanotechnologymentioning
confidence: 99%
“…Studies have found that slow release of GDNF and CNTF with nanotechnology can extend the duration of efficacy and significantly improve RGC survival in animal glaucoma models [109–112]. Nanomedicine has also improved delivery of antioxidant compounds used to treat glaucoma [113–116,117 ▪ ,118 ▪ ] and delivery of stem cells to the TM [119]. Nanotechnology could meaningfully improve the effectiveness of glaucoma treatment by improving the pharmacologic characteristics of drugs.…”
Section: Nanotechnologymentioning
confidence: 99%
“…For instance, D-NAC functionalized with triphenylphosphonium (TPP) can be incorporated with mitochondrial targeting ability, which enables D-NAC to localized selectively into the mitochondria of activated microglia/macrophages and attenuates neuroinflammation after systemic administration in a rabbit TBI model. [156] Since dendrimers can potentially be modified into a diagnostic agent for real-time visualization in vivo, [151,157] this suggested that it may be possible to develop D-NAC into a theranostic agent for TBI. [136] Copyright 2023, John Wiley & Sons, Inc.…”
Section: Dendrimer For Immunotherapymentioning
confidence: 99%
“…Ameboid-activated microglia and elevated expression of proinflammatory cytokines in postmortem glaucoma eyes have been reported [ 2 , 6 ]. Activated and proliferative microglia have been noted in the optic nerve and retina of experimental glaucoma animal models in the early stages of the disease, before RGC and axon loss [ 7 , 8 ]. Activated microglia can help clear cellular debris and secrete neuroprotective factors; however, with chronic persistent activation, their activation become irreversible and trigger secondary retinal and optic nerve damage.…”
Section: Introductionmentioning
confidence: 99%
“…Activated microglia can help clear cellular debris and secrete neuroprotective factors; however, with chronic persistent activation, their activation become irreversible and trigger secondary retinal and optic nerve damage. By modifying microglial activation, depleting microglia, and blocking microglial downstream, targeting microglia delays neurodegenerative processes in glaucoma animals [ 7 10 ]. Taken together, previous studies suggest the potential treatment strategies to target microglia in glaucoma.…”
Section: Introductionmentioning
confidence: 99%